Individuals with fibromyalgia have a different gait pattern and a reduced walk functional capacity: a systematic review with meta-analysis - Carrasco-Vega, Elio; Ruiz-Muñoz, María; Cuesta-Vargas, Antonio; Romero-Galisteo, Rita Pilar; González-Sánchez, Manuel (PeerJ, 2022)
Background: The aim of the present study was to perform a systematic review and meta-analysis comparing walking test performance and gait pattern between individuals with and without fibromyalgia (FM). Methodology: This systematic review was registered in PROSPERO with the following reference: CRD42018116200.The search for the scientific articles in this systematic review was carried out using the MEDLINE, SCOPUS, PEDRO, CINHAL and WEB OF SCIENCE databases. A combination of three conceptual groups of terms was used: (1) fibromyalgia; (2) walk (performance) tests; and (3) gait analysis. The included articles were analyzed for both functional and pattern of walking data of patients with FM. In order to provide a better estimate of the difference between individuals with and without FM on gait, a meta-analysis was performed on the 6MWT (6-minute walk test). Results: Thirty-six studies were analyzed, with a total population of 4.078 participants (3.369 FM and 709 individuals without FM). From a functional point of view, the 6MWT distance covered by the group of individuals without FM was significantly greater than that of the individuals with FM in all the analyzed studies. In addition, when comparing the results obtained in the gait pattern analysis, it was observed that individuals with FM walked slower, with a shorter stride length and lower cadence compare to individuals without FM. Conclusions: It is possible to affirm that individuals with FM perform walking tests differently than individuals without FM. It was observed that individuals with FM walk performing a cycle of shorter length and lower frequency, producing a slower gait, which results in a shorter distance traveled, in the same period of time, with respect to healthy subjects.
Keywords: Enfermos de fibromialgia; Marcha (Ejercicio); Assessment; Fibromialgia; Gait; Kinematic; Qualitative; Quantitative; Walk